DISTRIBUTION OF CONCENTRATION DISSOLVED RADON (222 Rn) IN WAYANG-WINDU GEOTHERMAL MANIFESTATIONS - AROFAT (NIM : 12113045), GAGAH
The discovery of the permaeble zone is helpful in determining the geothermal prospects. One method that can be used in estimating the permaeble zone of the rock is by measuring the concentration of dissolved Radon (222Rn) in the geothermal manifestation of the field. Primary data of the concentration of dissolved Radon (222Rn) in this study were obtained by measurement using RAD7 and RAD H2O. Data collection was conducted on August 1 to 4, 2017 at Wayang-Windu geothermal area. The manifestations measured by the concentration of dissolved Radon (222Rn) were 10 hot springs and 8 cold springs, the duration of data collection of the dissolved Radon (222Rn) concentration for one spring was 60 minutes. The concentration dissolved Radon (222Rn) data measurement results are processed by descriptive statistical methods between hot and cold springs to determine the distribution of concentration. Processing by Ordinary Kriging method is used to know the pattern of its distribution, then overlayed with analysis parameters. In this method combined between hot and cold springs. The analysis parameters used are lithology, hydrogeology, regional fault, subsurface structure, manifestation, topography and lineament of research area. Descriptive statistical results between hot and cold springs obtained concentrations of dissolved Radon (222Rn) in cold springs higher than hot springs that showed dissolved Radon (222Rn) in hot water degassing. The result of overlay of dispersion pattern of concentration of dissolved Radon (222Rn) then analyzed to know correlation with parameter analysis. The presence of a correlation between the concentration of dissolved Radon (222Rn) with the regional fault crossing of the research area, indicating a permeable zone in the area.